Reflections upon China's hegemony and international policy: the Belt and Road initiative as a pacific development strategy - Pires, Marcos Cordeiro [UNESP]; Paulino, Luis Antonio [UNESP] (Univ Nacl La Plata, Fac Law & Science, 2017)
The Belt and Road Initiative, proposed by China in 2013, is an audacious economic and geopolitical project aimed at expanding and strengthening regional cooperation in the Eurasian context and in the Pacific and Indian Ocean basins. The project has two axes: land and sea, respectively the Economic Belt of the Silk Road and the Maritime Silk Road in the 21st century. This Initiative provides an opportunity to analyze the context of China's foreign policy and the strategies established to achieve its long-term goals such as its peaceful development, the creation of a multipolar world order and the reaffirmation of Five Principles of Peaceful Coexistence , means with which it seeks to build a new model of relationship between great powers that helps overcome a supposed inevitability of the Thucydides Trap. For this, this article is divided in three sections, besides theintroduction and the concluding remarks. In the first section, we will seek to raise some ground on the historical foundations of China's current foreign policy formulation. In the second section, we will discuss the evolution of Chinese foreign policy by analyzing the documents and statements of its leaders since 1978, when the Reform and Openness process begins. Finally, we will look at the Belt and Road Initiative as an example of how in practice China seeks to create the means to reaffirm its pacifist and inclusive intentions in a rather troubled geopolitical context.
Keywords: China; hegemony; Thucydides' Trap; Belt and Road Initiative